"HRCT predictors of GGO surgical resection: Histopathological and molecular correlation in the era of lung sparing surgery". (April 2022) - Volterrani, L.; Guerrini, S.; Zanfrini, E.; Grassi, A.; Addamo, E.; Mathieu, F.; Gentili, F.; Bellan, C.; Spina, D.; Mazzei, M.A.; Luzzi, L.
Highlights: Ground-glass pulmonary opacities (GGOs) are increasingly encountered in routine clinical practice and an accurate differentiation between benign and malignant lesions is crucial. The GG component detected at HRCT examination is correlated respectively to a lepidic pattern and tumor grading. The correlation between the percentage of GG at HRCT and tumor behavior is confirmed by the significant difference of GG component according to the tumor grading. Pure and part-solid GGOs could benefit from less invasive and lung sparing surgery with nodal sampling. For GGOs a longer follow-up interval could be considered to assess the presence of a second primary tumor instead of the risk of disease recurrence. Abstract: Objectives: Ground-glass pulmonary opacities (GGOs) are increasingly encountered in routine clinical practice and an accurate differentiation between benign and malignant lesions is crucial. The aim of this study is to evaluate the relationship between radiological features and the actual biological behavior of these nodules. The secondary endpoint is to identify any radiological predictors able to choose the type of surgical resection and the extent of lymphadenectomy. Materials and Methods: This single-center retrospective study included all patients, who underwent high resolution computed tomography (HRCT) and surgical resection for GGOs between 2010 and 2020. Histopathological sampling focused on lesion size, histology, growth pattern, amount of lepidic component, percentage of ground-glass (GG), grade of tumor and proliferation index (Ki67). Results: In 56 patients enrolled, 65 lesions (15 pure GG and 50 part-solid) were resected (44 lobectomies, 9 anatomical segmentectomies, 12 wedge resections). A direct significant correlation was found between: the GG at HRCT and the amount of lepidic component (p < 0.0001; R = 0.305), the tumor grading and the lepidic component at HRCT (p = 0.003), the percentage of GG and the expression of Ki67 (p = 0.016), the lepidic percentage and the expression of Ki67 (p = 0.004; R = 0.223). A total of 609 lymph-nodes were removed (stations N1 and N2) and histopathological analysis was negative for nodal involvement in all cases. Conclusion: Pure and part-solid GGOs could benefit from less invasive and lung sparing surgery with just nodal sampling. These would reduce surgical complications and guarantee a better quality of life for the patient. The major limitations are the number of patients and the lack of a longer follow-up.